The Impact of the banking digitalization indicators disclosure on the market value of banks listed on the Egyptian Stock Exchange: An Applied Study - Zohry, Dr. Alaa Fathy; Fadel, Dr. Ahmed Mohamed Ibrahim; Khamis, Dr. Asser Ahmed (The journal of contemporary issues in business and government, 2021)
This research investigates the Impact of the banking digitalization indicators disclosure represented in the quantitative and financial indicators on the market value of the banks listed on the Egyptian Stock Exchange, using the (Tobin’s Q) model. To achieve the research objective, the descriptive-analytical method was adopted, in addition to using the data collected from the published financial and sustainability reports of the banks or those which were available on the banks’ websites, as well as the reports of the Central Bank of Egypt and the Egyptian Stock Exchange relating to the study sample. The sample consisted of (11) banks listed on the Egyptian Stock Exchange, and the study was conducted over (5) Quarterly periods from January 2020 until the end of March 2021. The most disclosed items were the quantitative indicators of the banking digitalization, represented in the number of the ATMs, the number of electronic payment cards, the number of electronic branches, the number of Internet Banking subscribers, the number of electronic Wallet subscribers, the number of the Mobile Banking subscribers, in addition to the financial indicators of the banking digitalization which represented in the value of the transactions of the ATM, the value of the transactions of electronic Wallet, the value of the transactions of Internet Banking and the value of the transactions of the Mobile Banking. These indicators were deemed independent variables. Correlation analysis and multiple regression analysis using the (SPSS) program were adopted for data processing and hypothesis testing. The results proved that the disclosure of banking digitalization indicators led to an increase of the informational content of the financial reports from (0.352) to (0.526), which means additional informative content of (17.5%) of the changes in the ratio of market value/book value of banks listed in the Egyptian Stock Exchange. Accordingly, it is recommended for the Disclosure Department of the Egyptian Stock Exchange to require the listed banks to disclose the indicators of the banking digitalization as it provides additional informative content about the capital adequacy, profitability, liquidity, assets quality, size, and age of the bank.